Implementing the Policy to Serve Citizens (BMW) in Tulang Bawang Regency: Public Service Innovation Study - Winarti; Murtir Jeddawi; Sampara Lukman; Agus Fatoni (International Journal of Science and Society, 2021)
This study examines the implementation of the "Move to Serve Citizens" (BMW) policy in assessing innovation in public services in Tulang Bawang Regency, Lampung Province. Government leadership in implementing the "Move to Serve Citizens" (BMW) policy was initiated in the RANPERDA RPJMD Tulang Bawang 2017-2024 which is also an arrangement to realize its vision-mission of regional heads to improve community welfare and optimal public services in Tulang Bawang district. Research on the implementation of mobile policies to serve residents in Tulang Bawang Regency (the study of public service innovation uses a mixed-method research type or is often referred to as a mixed method, a research approach that combines associates qualitative and quantitative forms with inductive-deductive thought processes. BMW policy has a significant effect on public services. The research findings revealed that the BMW policy variable, each indicator of this variable, is considered to determine the success of the policy objectives. It has been determined that it has been optimally used to implement the BMW policy by Tulang Bawang Regency successfully.